Controlling the Proximity of the Poor: Patterns of Micro-Segregation in Naples’ Upper-Class Areas - Thomas Pfirsch (Land, 2023)
Naples has been described as a symbol of the weak segregation of Mediterranean cities, which are marked by microscale segregation rather than neighborhood segregation. This paper focuses on the upper-class areas of Naples where, besides vertical segregation, other patterns of micro-segregation can be found and remain understudied. In such areas, Disadvantaged groups still concentrate into streets, blocks and enclaves of poverty that have resisted gentrification despite their location in the heart of upper-class nieghborhoods. Though self-segregation of the urban élite has sharply increased with globalization and postfordist capitalism, such patterns of segregation in well-off areas are largely unexplored. The paper is based on a mixed method. It uses census data to map the residential location of disadvantaged groups in Naples upper-class areas at the local scale. It also draws on ethnographic fieldwork to analyze the Neapolitan élites’ attitudes towards the proximity of the poor. The paper shows that the spatial proximity of the poor has long been accepted and promoted by the city élite as a way of maintaining social control over their patronage. But it is increasingly stigmatized as this control through proximity becomes more difficult for the decaying traditional Neapolitan élite. Residential proximity is now associated with increasing segregation in the use of public spaces. The paper discusses the theory of élite Urban Secession in globalization. In Naples, rather than Secession, the élite play a game of proximity and distance with the poor, using space as a means of social control.